A novel concept of introducing a fillet at the chimney base of solar updraft tower plant and thereby improving the performance: A numerical study. (December 2021) - Praveen, Vivek; Das, Pritam; Chandramohan, V.P.
Abstract: Solar updraft tower (SUT) plant is one of the potential technologies for carbon-free power generation. However, a conventional SUT plant is not economical due to its lower thermal performance. The present work provides an in-depth numerical investigation and thereby enhancing the thermal performance of the SUT plant. The real SUT plant (Manzanares, Spain) dimensions were considered for this three-dimensional analysis. Two models of the SUT plant were developed; Case 1 having no fillet, Case 2 having a 45° square fillet. Comparative analysis was done between Case 1 and Case 2 on various performance characteristics such as turbine power ( P the ), collector and overall efficiencies ( η coll, η o ). Higher updraft velocity (about 38.5% rise) was observed due to the provision of fillet in case 2. Also, case 2 produced a P the of 141 kW, η coll of 62% and η o of 0.25% which are with an enhancement of 73.3%, 48.44% and 72.4%, respectively. These abrupt variations in performance parameters proved that the fillet makes much impact on the SUT system and therefore it must be built on the base of the chimney. The results were compared with the existing experimental data and found promising agreement. Highlights: The effect of fillet near the chimney base of solar updraft tower (SUT) plant was analyzed. Two SUT models of without and with fillet were modelled and simulated. 38.5% of velocity enhancement was noticed in SUT with fillet case. An abrupt enhancement was noticed in all flow and performance parameters. The overall efficiency of the plant with fillet was improved to 72.4%.